A Brief History of Futures. (December 2015) - Schultz, Wendy L.
This article provides a brief overview of the development of futures thinking and futures studies as exploratory activities, as applied research, and as an academic field. Beginning with prehistory, the narrative divides the development of futures work into five waves: (1) the oral tradition, (2) the early written age, (3) enlightenment and extraction, (4) systems and cybernetics, and (5) complexity and emergence. It also highlights in broad strokes the intellectual, cultural, political, economic, technological, and social contexts that informed the evolution of futures thinking.